THE FEASIBILITY OF SUPARDI'S TEMPEH BUSINESS IN BANJARBARU - Misransyah, Misransyah; Jumiati, Jumiati; Bulkis, Siti (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2023)
The research aims to determine whether or not the business is feasible from the quantitative descriptions from the financial aspect. The research methodology used is a survey method. The location of this research is on Jalan Rukun Mufakat RT. 003 RW. 003 South Banjarbaru District, Banjarbaru City. Supardi's Tempeh Business. Research uses primary data. Data collection techniques are by means of interviews, observations, questionnaires and literature studies. Method literature related to research methods. Technique Data analysis. The methods for calculating the Financial Aspects are: Calculation of the research results shows average income Rp.255.200.000,- and expenses Rp.199.314.000 per year. Net Present Value (NPV) of Rp. 37,401,900, -, Internal Rate Of Return (IRR) of 18.92%, Net Benefit Cost Ratio (Net B/C) of 2.9, Profitability index ( PI) of 1.9. From the calculation of the feasibility of the business above, it shows that Supardi's Tempeh Business is feasible to run its business.